Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts prepared with different precipitating agents - Tangale, Nilesh P.; Niphadkar, Prashant S.; Deshpande, Shilpa S.; Joshi, Praphulla N. (Applied Catalysis A-General, 2013)
Dehydrogenation of cyclohexanol over Cu/Al2O3 catalysts (molar Cu:Al = 1:1) prepared by reduction of mixed oxide precursors synthesized using different precipitating agents viz, potassium carbonate, tetraalkyl ammonium hydroxides (TAAOHs) and urea was investigated. In order to assess the efficacy of TAAOH further, the chain length of tetraalkyl ammonium cations was also varied and the resulted catalysts were evaluated for their catalytic performance. The catalysts were characterized by powder X-ray diffraction, low temperature nitrogen adsorption, temperature programmed desorption of ammonia and UV-visible diffuse reflectance spectroscopy. The dependence of the catalyst performance on the precipitating agent employed during its synthesis has been clearly demonstrated. The use of TAAOH as precipitating agent led to the formation of a catalyst with better catalytic activity than those prepared using potassium carbonate and urea. Further improvement in the catalytic performance was observed when TAAOH with longer alkyl chain ammonium cation was used. The optimum catalyst prepared by reduction of mixed oxide precursor synthesized using tetrapropyl ammonium hydroxide as precipitating agent, showed highest cyclohexanol conversion (81.5%) and cyclohexanone selectivity (79.6%) at 250 degrees C on account of higher Cu+/Cu-0 ratio, well dispersed copper, higher surface area and lower total acidity with higher contribution of sites with moderate strength. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Characterization; Cu/Al2O3; Cyclohexanol dehydrogenation; Precipitating agent; Tetraalkyl ammonium hydroxide